Preservice physical education teacher socialization through an outdoor education field experience. Issue 4 (2nd October 2018) - R. Richards, K. Andrew; Jacobs, Jennifer M.; Wahl-Alexander, Zachary; Ressler, James D.
ABSTRACT: Outdoor education (OE) has an increased presence in physical education as it addresses the discipline's national standards and promotes involvement lifetime physical activity. However, physical educators' learning to teach OE is not well documented. The purpose of this study was to understand preservice physical educators' experiences in and perspectives on an OE field experience. Participants included 13 third-year preservice physical educators (10 male, 3 female). Qualitative data were collected using focus group interviews, observations and guided reflections. Results indicated that preservice teachers (PSTs) perceived a controlling course environment that limited educational outcomes. They did, however, increase in confidence teaching OE, and applied skills learned in the teacher education program. With the exception of learning to be more adaptable, however, the PSTs did not perceive the experience as relevant to future teaching. Results are discussed within the framework of occupational socialization theory, and implications for practice are noted.